Co‐occurrence of immune‐mediated conditions and endometriosis among adolescents and adult women. (25th February 2021) - Shafrir, Amy L; Palmor, Marissa C.; Fourquet, Jessica; DiVasta, Amy D.; Farland, Leslie V.; Vitonis, Allison F.; Harris, Holly R; Laufer, Marc R.; Cramer, Daniel W.; Terry, Kathryn L.; Missmer, Stacey A.
Abstract: Problem: Associations between immune dysfunction conditions (eg, systemic lupus erythematous, rheumatoid arthritis) and endometriosis have been observed in adult women, but not assessed among a younger population. We investigated the association between immune‐mediated conditions and endometriosis among young women. Method of Study: This cross‐sectional analysis in the Women's Health Study: From Adolescence to Adulthood included 551 participants with surgically diagnosed endometriosis (median age=19) and 652 controls without endometriosis (median age=24). Participants completed an expanded Endometriosis Phenome and Biobanking Harmonization Project questionnaire. We used logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) to investigate the associations between autoimmune/inflammatory, atopic, chronic pain/fatigue, and endocrine disorders with endometriosis, adjusting for confounders. Results: Participants with any autoimmune and/or inflammatory condition had an increased odds of co‐occurring endometriosis (OR: 1.87; CI: 0.92–3.80), as did participants with allergies (OR: 1.76; CI: 1.32–2.36), asthma (OR: 1.35; CI: 0.97–1.88), chronic fatigue syndrome and/or fibromyalgia (OR: 5.81; CI: 1.89–17.9), or previous mononucleosis (OR: 1.75; CI: 1.14–2.68). Odds of endometriosis were lower among participants with eczema (OR: 0.68; CI: 0.44–1.04). We observed a positive trend between the number of immune‐mediated conditions and the odds of endometriosis (p‐trend=0.0002). Endocrine disorders were not associated with endometriosis. Conclusions: Among this population of adolescents and adult women, endometriosis was more likely among participants with autoimmune and/or inflammatory diseases, allergies, asthma, previous mononucleosis infection, and chronic fatigue and/or fibromyalgia. We observed that an increasing number of immune‐mediated conditions were positively associated with endometriosis risk. It is important for clinicians who care for adolescents and women with these conditions to consider endometriosis as a comorbidity.